2018
DOI: 10.1111/ctr.13391
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, frailty, and adverse outcomes among kidney transplant recipients

Abstract: Depressive symptoms and frailty are each independently associated with morbidity and mortality in kidney transplant (KT) recipients. We hypothesized that having both depressive symptoms and frailty would be synergistic and worse than the independent effect of each. In a multicenter cohort study of 773 KT recipients, we measured the Fried frailty phenotype and the modified 18-question Center for Epidemiologic Studies-Depression Scale (CES-D). Using adjusted Poisson regression and survival analysis, we tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 39 publications
(57 reference statements)
1
49
0
8
Order By: Relevance
“…The effect of frailty on length of stay is especially pronounced in patients with depressive symptoms (1.9 fold increase in risk). 23 Pre-transplant hospitalization, a surrogate measure of frailty, is also associated with increase post-transplant hospitalization (0 hospital days: 73%; 1–7 days: 70%; 8–14 days: 75%; ≥15 days: 80% hospitalization by 12 months of transplant) 24 .…”
Section: Frailty and Outcomes After Transplantmentioning
confidence: 99%
“…The effect of frailty on length of stay is especially pronounced in patients with depressive symptoms (1.9 fold increase in risk). 23 Pre-transplant hospitalization, a surrogate measure of frailty, is also associated with increase post-transplant hospitalization (0 hospital days: 73%; 1–7 days: 70%; 8–14 days: 75%; ≥15 days: 80% hospitalization by 12 months of transplant) 24 .…”
Section: Frailty and Outcomes After Transplantmentioning
confidence: 99%
“…Among kidney transplantation (KT) candidates, frailty is associated with decreased access to KT [19], waitlist mortality [19-21], cognitive impairment [22], and poor health-related quality of life [23]. KT recipients who are frail at the time of admission for transplantation are more likely to experience depressive symptoms [24], poor health-related quality of life [25], longer length of stay [26], delirium [27], delayed graft function [28], reduction in mycophenolate mofetil immunosuppression dose [29], early hospital readmission [30], and mortality [31, 32]. Importantly, the association between frailty and these adverse outcomes does not differ by whether the patients were older or younger, suggesting that frailty is equally as predictive for older and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Potential causes of frailty in chronic kidney disease patients have been reported to be age, sex, BMI, education, comorbidities, serum creatinine levels, serum testosterone levels, serum albumin levels, depression and disability. [14][15][16][17]22,23 A priori, we selected seven covariates, including age, sex, BMI, time after transplant, dialysis duration before transplant, eGFR and serum albumin levels, to avoid overfitting. Multivariable analysis showed that dialysis duration was positively correlated with frailty.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that kidney transplant recipients with depressive symptoms were more likely to have frailty, and kidney transplant recipients who had both frailty and depression were associated with increased adverse outcomes. 23 Furthermore, the KCL is beneficial, because it is an easy-to-answer self-reported questionnaire, and it might be an appropriate assessment for frailty in kidney transplant recipients at outpatient departments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation